Utilization of Library Resources among Students of Government Senior Secondary School Kyan Rikkos, Jos Plateau State, Nigeria - Favour Ehi Attah; Shittu Lukman Olayinka; Muhammad Daud (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2024)
This study examined the utilization of library resources among students of Government Senior Secondary School Kyan Rikkos, Jos, Plateau State, Nigeria, addressing three research questions. A descriptive survey research design, specifically a cross-sectional survey, was employed. The study population comprised 314 senior secondary school students, with a sample of 100 students selected through simple random sampling. The sample included 30 students from SS I, 40 students from SS II, and 30 students from SS III. Data collection was conducted using a structured questionnaire titled Questionnaire on Utilization of Library Resources among Students of Government Senior Secondary School (SQULRS). The instrument underwent face and content validation and achieved a reliability coefficient of 0.81. Data were analyzed using simple percentages, frequency counts, and mean methods. Findings revealed that the use of library resources significantly influences students' academic achievements, educational progress, comprehension, overall knowledge, and intellectual capacity. The study also highlighted varied student perceptions of library resources, with some viewing them as essential materials and equipment, while others saw them as tools to enhance learning. The study concluded that the utilization of library resources is affected by various internal and external factors. It recommended that school administrators actively encourage library usage among students and that parents and teachers promote library engagement to support students’ intellectual development.